Efficacy of Trichoderma isolates against Sclerotium rolfsii causing collar rot of lentil - Aryal, Laxman; Baidya, Suraj; Subedi, Subash (Journal of Agriculture and Natural Resources, 2022)
Lentil collar rot disease caused by Sclerotium rolfsii Sacc. is an important disease causing significant yield loss in Nepal. Seven Trichoderma spp. isolates collected from different regions of Nepal were tested for their capacity to inhibit mycelial growth of Sclerotium rolfsii in in-vitro condition. Experiment was conducted in Completely Randomized Design with four replications in the plant pathology laboratory of Grain Legumes Research Program, Khajura, Banke during 2020. Dual culture method was performed to assess the efficacy of Trichoderma isolates. Trichoderma spp. isolates inhibited mycelial growth of S. rolfsii to various degrees ranging from 48.33-72.47% after 120 hours of inoculation. Maximum colony inhibition of S. rolfsii (72.47%) was obtained by Kapilvastu isolate followed by Nepalgunj isolate (67.72%). Minimum colony inhibition of S. rolfsii (48.33%) was obtained by Mangalpur, Chitwan isolate followed by Rampur, Chitwan isolate (49.33%). Among seven Trichoderma isolates, two isolates (Kapilbastu and Nepalgunj) showed good antagonistic activity against S. rolfsii and were also highly competitive in in-vitro condition. These isolates would therefore be useful in biological disease management.